Decentralising distribution of publications - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
CTA has set itself the long-term target of shifting the distribution of its publications from a centralised system to a web including involving local partners in ACP countries. An early step in this strategy has been taken with the conclusion of a...